1994
DOI: 10.2105/ajph.84.11.1839
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis Nigricans among Native Americans: an indicator of high diabetes risk.

Abstract: Prevalence of the skin lesion acanthosis nigricans was determined in two tribal communities in Texas and Nebraska. Thirty-eight percent of the Alabama-Coushatta tribe of Texas had acanthosis nigricans. Nineteen percent of Omaha and Winnebago tribal children had the skin lesion; the youngest children had the least acanthosis nigricans. Among weight-matched Alabama-Coushatta, fasting insulin concentrations were twofold higher in subjects with the lesion. It was concluded that acanthosis nigricans is highly preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
3
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 29 publications
6
88
3
9
Order By: Relevance
“…The prevalence of AN in the present study was 41.7%, greater than that reported by Stoddart et al, who found 34.2% AN in a Cherokee Indian population (25). Meanwhile, Mukhtar et al documented an 18.9% prevalence of AN in obese adolescents in New Mexico (26), Nguyen et al reported 25% of AN in overweight Afro-American children (27), and Stuart et al found 38% of AN in Native Americans (28). On the other hand, Thivel D and Maisonneuve B have reported the prevalence of AN to be as high as 68 and 69.9%, respectively, in obese children (29,30).…”
Section: Discussioncontrasting
confidence: 66%
“…The prevalence of AN in the present study was 41.7%, greater than that reported by Stoddart et al, who found 34.2% AN in a Cherokee Indian population (25). Meanwhile, Mukhtar et al documented an 18.9% prevalence of AN in obese adolescents in New Mexico (26), Nguyen et al reported 25% of AN in overweight Afro-American children (27), and Stuart et al found 38% of AN in Native Americans (28). On the other hand, Thivel D and Maisonneuve B have reported the prevalence of AN to be as high as 68 and 69.9%, respectively, in obese children (29,30).…”
Section: Discussioncontrasting
confidence: 66%
“…The first large-scale study of AN in an American Indian population found AN in 38% of 260 members (10 -70 years of age) of the Alabama-Coushatta tribe in Texas and 1,141 children (3-19 years of age) of the Winnebago/Omaha tribe in Nebraska (16). In addition, they found a twofold higher fasting insulin concentration in subjects who exhibited AN than in weight-matched subjects who did not have the skin condition, concluding that AN was highly prevalent among American Indians and that its presence suggests insulin resistance and an increased risk for type 2 diabetes.…”
Section: Prevalence Of Hyperinsulinemiamentioning
confidence: 99%
“…AN is common among AfricanAmericans, Hispanics, and American Indians but rare among whites (7, 9 -11,15,17) and has been reported to be strongly influenced by genetic factors (19). Previously thought to be rare in children and adolescents (14), AN is now common in young people, especially in populations with high rates of adult diabetes (7,10,11,16,18).…”
mentioning
confidence: 99%
“…AN in any place in the body is taken as an overall diagnosis; unfortunately, many times the knuckles are overseen and obviated in physical examination. 13 , 16 , 18-22 In fact, without reliable evidence, some authors mention that AN does not exist unless the neck is involved. 16 , 23 They recommend just examining the neck when a clinician is looking for AN.…”
Section: Discussionmentioning
confidence: 99%
“…14 , 22 , 27-30 There is a paucity of evidence, however, on the clinical epidemiology of AN. For example, AN prevalence among different BMI or age ranges, different anatomical sites, subjects with 1 or 2 skin phototypes, varieties of clinical expression in these two phototypes, and as a diagnostic tool beyond the link to hyperinsulinemia in overweight or obese subjects.…”
Section: Discussionmentioning
confidence: 99%